2011
DOI: 10.1177/0269215511421029
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of electrostimulation effects on effussion, swelling and pain recovery after anterior cruciate ligament reconstruction: a pilot study

Abstract: Electrostimulation along with exercise therapy appears superior to exercise alone regarding knee effusion, swelling and pain recovery after anterior cruciate ligament reconstruction. Still, there is need for further clinical studies using a radiologic method to demonstrate this effect of electrostimulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 22 publications
0
22
1
1
Order By: Relevance
“…The level A2 RCT of Paternostro-Sluga et al 100 and the level B RCT of Fitzgerald et al 99 were included in both systematic reviews. Ediz et al 97 (level B RCT) and Lepley et al 102 (level C prospective cohort study) found no differences in effusion, pain, ROM and knee extension and flexion moments when electrostimulation was added to conventional rehabilitation. Feil et al 98 and Taradaj et al 101 (both level B RCTs) did examine quadriceps strength and found a higher increase in quadriceps strength when electrostimulation was added to conventional rehabilitation at a 6-month follow-up.…”
Section: Resultsmentioning
confidence: 98%
“…The level A2 RCT of Paternostro-Sluga et al 100 and the level B RCT of Fitzgerald et al 99 were included in both systematic reviews. Ediz et al 97 (level B RCT) and Lepley et al 102 (level C prospective cohort study) found no differences in effusion, pain, ROM and knee extension and flexion moments when electrostimulation was added to conventional rehabilitation. Feil et al 98 and Taradaj et al 101 (both level B RCTs) did examine quadriceps strength and found a higher increase in quadriceps strength when electrostimulation was added to conventional rehabilitation at a 6-month follow-up.…”
Section: Resultsmentioning
confidence: 98%
“…NMES waveform: low-frequency biphasic 95,97,98,101,[104][105][106][107] or medium-frequency burst-modulated AC 99,103,[108][109][110] Frequency: 30-50 Hz PC 95,97,101,[104][105][106][107] or 2500 Hz AC in 50 Hz bursts 99,110,111 Pulse duration: 250-400 ms 97,100,102,103,[105][106][107]112,113 Current amplitude: individual max tolerated intensity; minimum at strong but comfortable muscle contraction 95,97,99,100,105,106,109,112,113 Work-rest cycle: ON:OFF 6-10:12-50 s; 95,98,101,103,105,106 use lower duty cycle-e.g., work-rest 1:3-1:5-if the muscle is weaker to limit fatigue associated with an e...…”
Section: A Anterior Cruciate Ligament Reconstructionmentioning
confidence: 99%
“…Treatment schedule: initiate ideally within 1 wk post-op: [98][99][100][101] 12-15 contractions/session 98,99,102,103,[108][109][110]112 Session frequency: 3 Â wk over 4-6 wk, particularly in the first 6 wk post-op 98,101,110 e Reduced pain (NPRS, VAS) 98,105 e Improved muscle strength (isometric and isokinetic, dynamometry, tensiometry) 99,100,[102][103][104][107][108][109][110]112,113 e Reduction in loss of muscle volume or thickness (CT, MRI, US imaging) 100,107,113 e Self-reported function (ADL scale) 108 e Gait parameters (motion analysis) 103 e Achieving clinical milestones 108 e Limb circumference (tape measure) 105,110 e Functional performance (lateral step-up, anterior reach) 100,101 Rationale for recommended NMES protocol…”
Section: A Anterior Cruciate Ligament Reconstructionmentioning
confidence: 99%
See 1 more Smart Citation
“…NMES using percutaneous electrodes is noninvasive and easy-to-use, and has reportedly shown good results in preventing muscle weakness and decreasing the thickness of the quadriceps muscle after anterior cruciate ligament surgery. [10][11][12][13][14][15] We therefore hypothesized that NMES could prevent deltoid muscle atrophy after arthroscopic rotator cuff repair, and performed a single-blind randomized study to compare the decrease in deltoid thickness in the NMES group and the transcutaneous electrical nerve stimulation (TENS) group (control).…”
Section: Introductionmentioning
confidence: 99%